A gestão de serviços em hospitalidade: o papel do comissário como anfitrião nas empresas aéreas brasileiras - SALVA, Viviane (2017)
The aim of this research was to identify how hospitality articulates within Brazilian aircraft through the relationships established between the cabin crew and the clients of the airlines that make up ABEAR. The intention with the research was to understand what would be the real function of the flight attendant and whether he could be identified as the host of the airline, considering that in addition to being responsible for flight safety, the flight attendant is the intermediary between the Company and customers, and in turn is this professional who generally stays with the customer of an airline for a longer period. Its on-board function allows hospitality to play a complementary role to control the mechanisms of oversight, whose goal is to maintain flight safety. Throughout this research we tried to confirm or refute the following propositions: a) aircraft environment can be considered a place of reception; b) the training that the cabin crew receives can be considered a tool to develop the capacity to be hospitable; c) hospitality times may be considered to characterize the flight attendant as the host; d) the hospitality offered on board may represent or suggest certain passenger control mechanisms. The methodological procedures chosen indicate an exploratory research and a qualitative approach. A bibliographical research was carried out. The objective was to construct the theoretical reference in relation to hospitality. The websites of the airlines and the aviation documents were also investigated. For the research, the documents related to the flight attendants were analyzed; semi-structured interviews were carried out, firstly in a pre-test that guided the format of the final interviews. The final interviews were carried out with the President of ABEAR, flight attendants and with clients of the airlines, analysis of documents related to flight attendants was used documentary and bibliographical analysis, for the interpretation of the interviews was used the content analysis of Foucault (2012). It is concluded that flight attendants may represent the principal host of an airline but is not considered to be the only host. It was also concluded that flight safety is within the universe of hospitality, as one of the attributes of the host is the protection of the guest.